The Difference in Engagement Levels and Youth SelfActualization in Islamic University Organizations in Cirebon - Windiana, Wiwin; Rihifuddin, Syauqi Asfiya'; Nugraha, Muhammad Iqbal (Mimbar Agama Budaya, 2024)
This research aims to investigate differences and correlations in engagement levels within university organizations among PMII members across Islamic State and private higher education institutions in Cirebon, as well as differences in their self-actualization. The research employs a quantitative approach with systematic random sampling. A sample of 285 participants was selected from a population of 1070 PMII members at these institutions with analysis techniques involving the Mann-Whitney U test for the first and second research questions, and Spearman’s correlation for the third. Results indicated a statistically significant difference in engagement levels within organizations between Islamic state and private higher education (U = 7193.500, z = -2.263, p = .024), suggesting higher engagement among Islamic state students. However, no significant difference was found in self-actualization levels between these groups (U = 5128, z = -.166, p = .868). Moreover, a strong positive correlation was observed between engagement levels within organizations and self-actualization among PMII members in both Islamic state and private institutions (rs = .525, p < .001).